(untitled) (Journal of Educational Sciences, 2024)
Structural -content model of the development of professional competences of the personality of pre-service social educators to work in conditions of inclusive education is described in the article. The proposed model was developed on the basis of a comparative analysis of the preparation of social educators to work in the conditions of inclusive education in the Republic of Kazakhstan, Lithuania and Germany, and helps to fix the initial state of the development of professional competences of pre-service social educators to work in the conditions of inclusive education. The model as a component became the basis for designing the process of developing professional competences of pre-service social educators to work in conditions of inclusive education. Based on the developed models, experimental work was organized to develop the professional competencies of pre-service social educators to work in conditions of inclusive education. 68 bachelor students of the educational program “Social Pedagogy and Self-cognition” of Al-Farabi Kazakh National University (34 students) and Abay Kazakh National Pedagogical University (34 students) took part in the experiment . The result of the experimental study is a high level of development of professional competences of pre-service social educators to work in conditions of inclusive education, such as social and communicative competences, organizational competences, system competences, intervention competences, competences in the field of development and training. Keywords: inclusive education, pre-service social educators, professional competences,structural - content model.